Negatywna telewizyjna reklama polityczna w wyborach do Parlamentu Europejskiego w Polsce w 2009 roku - Friedrich, Marek (Polityka i Społeczeństwo, 2021)
Negative television political advertising has become an instrument commonly found in election campaigns in most democratic countries around the world. This article is intended to show the functioning of this element of political marketing, focusing in par-ticular on its presence on Polish soil. This article indicates the genesis of negative televi-sion political advertising, its nature, significance, and provides an analysis that included sample ads by the campaign staffs of Law and Justice, Civic Platform and Democratic Left Alliance, which were broadcast during the election campaign before the election to the European Parliament in 2009.